Exploring the Strategies to Empower the Mothers of Adolescent Girls with Hearing Impairment to Deal with their Social and Emotional Problems - Ashraf, Samina; Iqbal, Kashif; Jahan, Musarrat (Pakistan Journal of Humanities and Social Sciences, 2023)
Hearing impairment affects the social and emotional life of an individual with hearing impairment, particularly girls. Mothers have the primary role of supporting their children with hearing impairment in the adolescent life stage so that these children could cope with their social and emotional problems. This study intended to seek the challenges faced by mothers of adolescent girls with hearing impairment and to empower the mother in dealing with the social and emotional problems of their adolescent girls with hearing impairment. This study was qualitative and exploratory. The sample of the study included 20 mothers of adolescent girls with hearing impairment. The purposive sampling technique was used to collect data for this study. The tool for data collection was a self-developed semi-structured interview protocol. The validity of the interview protocol was assured by the expert opinion (N=03). The reliability was confirmed through an extensive literature review. Data were analyzed through coding and thematic analysis. Open coding was used during the coding analysis. Three major themes appeared in the data analysis; challenges, efforts of mothers, and mothers' empowerment through coping strategies. The findings of the study revealed that the majority of the mothers have experienced various problems including communication difficulties, lacking knowledge about hearing impairment, and emotional disturbance of their adolescent girls with hearing impairment due to non-acceptance by society and social pressures. Additionally, mothers expressed that their adolescent girls with hearing impairment experience various social and emotional problems including bullying and non-supportive behavior in a society that perpetrates stress and anxiety among them. The study recommended special training and guidance sessions to empower the mothers of hearing-impaired girls.